Tick Paralysis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Six children aged 3.3 to 5.5 years (5 girls and 1 boy), of 26 admitted with acute muscle weakness to the University of Mississippi Medical Center, Jackson, over a 5 year period (1992-97), were diagnosed with tick paralysis.